2022
DOI: 10.1038/s41419-022-04766-0
|View full text |Cite
|
Sign up to set email alerts
|

HspBP1 is a dual function regulatory protein that controls both DNA repair and apoptosis in breast cancer cells

Abstract: The Hsp70-binding protein 1 (HspBP1) belongs to a family of co-chaperones that regulate Hsp70 activity and whose biological significance is not well understood. In the present study, we show that when HspBP1 is either knocked down or overexpressed in BRCA1-proficient breast cancer cells, there were profound changes in tumorigenesis, including anchorage-independent cell growth in vitro and in tumor formation in xenograft models. However, HspBP1 did not affect tumorigenic properties in BRCA1-deficient breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Similarly, KDM1A inhibition is effective in reducing stemness and treating TNBC ( 42 ). Decreased HSPBP1 may lead to genomic instability and enables resistance to ionizing radiation in high-grade and metastatic BC ( 43 ). Therefore, these hub genes may associate with ZSCAN18 and play important roles in BC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, KDM1A inhibition is effective in reducing stemness and treating TNBC ( 42 ). Decreased HSPBP1 may lead to genomic instability and enables resistance to ionizing radiation in high-grade and metastatic BC ( 43 ). Therefore, these hub genes may associate with ZSCAN18 and play important roles in BC.…”
Section: Discussionmentioning
confidence: 99%
“…HspBP1 regulates the phosphorylation of the tumor suppressor BRCA1 and its subsequent recruitment to DNA damage sites. It was recently shown that HspBP1 inhibits, in a BRCA1-dependent manner, the tumorigenesis of breast cancer in vitro and in vivo and promotes apoptosis [ 50 ]. Although we did not observe any clear change in HspBP1 levels between GBM and normal brain tissues, our LC-MS/MS analysis demonstrated ST1926 up-regulated HspBP1 levels in U251 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a recent report on the ratio of iHSP70 to eHSP70 and inflammation [56]. When cells undergo stress, iHSP70 present in cells is transferred to the circulation system through mechanisms such as cell necrosis and ATP-binding cassette (ABC) transporters [57,58]. This HSP was named eHSP70.…”
Section: Chronic Inflammationmentioning
confidence: 99%